The effectiveness of fiscal policy within business cycle – Ricardians vs. non-Ricardians approach. Issue 2 (3rd July 2019) - Krajewski, Piotr; Szymańska, Agata
ABSTRACT: This study aims to measure the impact of the share of non-Ricardian households on fiscal multipliers. We show that the share of non-Ricardian households in Hungary increased significantly after crisis began and explain why the plausible reason for this increase is the higher level of liquidity constraints during crisis. We also show that after crisis, when the share of non-Ricardians in Hungary was very high, the impact of government spending shocks on GDP was almost twice as strong as before the Great Recession. Thus, the results of the study indicate that there is some trade-off between the effectiveness of fiscal policy as a tool of GDP stabilization and household access to the credit market.